2017
DOI: 10.15835/nsb9110025
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Assessment of Poultry Feeds within Ilorin, Nigeria

Abstract: The poultry feeds were obtained from 20 different poultry pens and their microbial contents were assessed. The antibiotics resistance patterns of the bacterial isolates were also determined. The bacterial count ranged from 5.0 × 103 to 1.76 × 106 cfu/g while the fungal count ranged from 3.5 × 104 to 1.9 × 105 cfu/g. The bacterial species isolated were Streptococcus salivarius, Streptococcus pyogenes, Micrococcus luteus, Micrococcus varians, Micrococcus roseus, Staphylococcus aureus, Staphylococcus saprophyticu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 5 publications
2
10
1
Order By: Relevance
“…Only Tetracyclines are allowed for use in poultry for prevention of disease and as growth promoters because they are not classified as important for humans [35]. Unfortunately, this study observed multiresistance by most isolates to a lot of these drugs that are prohibited for use (Table 3) in agreement with [36] in earlier work in Ghana and [19] in Nigeria. This finding suggests that recommendations by WHO [35] are not being complied with.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Only Tetracyclines are allowed for use in poultry for prevention of disease and as growth promoters because they are not classified as important for humans [35]. Unfortunately, this study observed multiresistance by most isolates to a lot of these drugs that are prohibited for use (Table 3) in agreement with [36] in earlier work in Ghana and [19] in Nigeria. This finding suggests that recommendations by WHO [35] are not being complied with.…”
Section: Discussionsupporting
confidence: 88%
“…This finding agrees with the general view that poultry feed is prone to microbial contamination along the value chain, from the environment, during transport, and storage on the farm and cross contamination from wild birds, insects, rodents, etc. [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…Yeast counts was indicated to be high in site G and lower in F which is due to the direct exposure to air of sample G. Sule et al (2015), reported that, dusty unhygienic environment coupled with poor handling by vendors are factors contributing to high microbial load. However, Mold counts were indicated to be high in site A and low in site D this may be attributed to humidify air concentration.…”
mentioning
confidence: 96%
“…In BC, the most frequent was Corynebacterium xerosis, then Micrococcus varians, and lastly Bacillus species and Corynebacterium xerosis was also most frequent, then Micrococcus varians, then the rests. Thus, Corynebacterium xerosis was the most overall prevalent, then M. varians, then the rests Sule and Ilori (2017). determined Micrococcus species (more particularly M.varians) from poultry feed in Ilorin Nigeria.…”
mentioning
confidence: 97%
“…Poultry is a source of food that has been accepted worldwide through the ages. The consumption of poultry products is increasing every year and consumers want a safe product, thus it is pertinent that the poultry producers achieved this goal .Often, poultry products are involved in human foodborne poisoning/diseases posing a considerable cost and threat to public health (International Consultative Group on Food Irradiation, 1999; Ventura daSilva, 2013; Sule and Ilori, 2017). Increase in contacts of poultry with microbes lead to increased contact rates with humans and open new avenues for introduction, proliferation, and transmission of pathogens ; and ultimately more threats to public health (The PEW Charitable Trusts, 2016).…”
mentioning
confidence: 99%